Dentate gyrus norepinephrine ramping facilitates aversive contextual processing - Eric T. Zhang; Grace S. Saglimbeni; Jiesi Feng; Yulong Li; Michael R. Bruchas (Nature Communications)
Abstract Dysregulation in aversive contextual processing is believed to affect several forms of psychopathology, including post-traumatic stress disorder (PTSD). The dentate gyrus (DG) is an important brain region in contextual discrimination and disambiguation of new experiences from prior memories. The DG also receives dense projections from the locus coeruleus (LC), the primary source of norepinephrine (NE) in the mammalian brain, which is active during stressful events. However, how noradrenergic dynamics impact DG-dependent function during contextual discrimination and pattern separation remains unclear. Here, we report that aversive contextual processing in mice is linked to linear elevations in tonic norepinephrine release dynamics within the DG and report that this engagement of prolonged norepinephrine release is sufficient to produce contextual disambiguation, even in the absence of a salient aversive stimulus. These findings suggest that spatiotemporal ramping characteristics of LC-NE release in the DG during stress likely serve an important role in driving contextual processing.